Comparison of effects of midostaurin, crenolanib, quizartinib, gilteritinib, sorafenib and BLU‐285 on oncogenic mutants of KIT, CBL and FLT3 in haematological malignancies. (15th July 2019) - Weisberg, Ellen; Meng, Chengcheng; Case, Abigail E.; Sattler, Martin; Tiv, Hong L.; Gokhale, Prafulla C.; Buhrlage, Sara J.; Liu, Xiaoxi; Yang, Jing; Wang, Jinhua; Gray, Nathanael; Stone, Richard M.; et al.
Summary: Mutations in two type‐3 receptor tyrosine kinases (RTKs), KIT and FLT3, are common in both acute myeloid leukaemia (AML) and systemic mastocytosis (SM) and lead to hyperactivation of key signalling pathways. A large number of tyrosine kinase inhibitors (TKIs) have been developed that target either FLT3 or KIT and significant clinical benefit has been demonstrated in multiple clinical trials. Given the structural similarity of FLT3 and KIT, it is not surprising that some of these TKIs inhibit both of these receptors. This is typified by midostaurin, which has been approved by the US Food and Drug Administration for mutant FLT3‐positive AML and for KIT D816V‐positive SM. Here, we compare the in vitro activities of the clinically available FLT3 and KIT inhibitors with those of midostaurin against a panel of cells expressing a variety of oncogenic FLT3 or KIT receptors, including wild‐type (wt) FLT3, FLT3‐internal tandem duplication (ITD), FLT3 D835Y, the resistance mutant FLT3‐ITD+ F691L, KIT D816V, and KIT N822K. We also examined the effects of these inhibitors in vitro and in vivo on cells expressing mutations in c‐CBL found in AML that result in hypersensitization of RTKs, such as FLT3 and KIT. The results show a wide spectrum of activity of these various mutations to these clinically available TKIs.